A review and classification of analytical methods for climate change adaptation. (13th November 2014) - Hinkel, Jochen; Bisaro, Alexander
<x xml:space="preserve">Abstract</x> The exchange of coherent arguments about methods applied in the field of climate change adaptation is challenging due to the growing diversity of analytical methods applied from natural science and social science. This is further complicated by the abstract and ambiguous terms, such as vulnerability and adaptive capacity, employed in the literature and the inadequate consideration given to the wider array of social science methods that are being applied now that adaptation has become a practical necessity. To address these limitations, a review and novel classification of vulnerability, impacts, and adaptation methods is presented. Methods are classified based on goals addressed, thematic clusters of variables involved, and underlying theoretical assumptions. On the top‐level, methods are distinguished into impact analysis, behavior analysis, institutional analysis, and decision analysis methods. The first three branches are further classified according to descriptive, explanatory, and predictive goals, as well as theoretical assumptions. For each type, empirical conditions of applicability and examples from the literature are presented. While this classification can only be partial due to the ever growing methodological diversity in the field of climate change adaptation, we provide a more rigorous basis for the coherent exchange of methodological arguments and thereby hope to foster the interdisciplinary dialog needed to advance the field. WIREs Clim Change 2015, 6:171–188. doi: 10.1002/wcc.322 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.